(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Renal involvement is a rare complication of β-thalassemia. Both tubular and glomerular dysfunction might occur in these patients. The aim of this study was to evaluate and compare kidney function in the major, intermedia, and minor variants of β-thalassemia. Materials and Methods. Renal tubular and glomerular function of 72 patients with β-thalassemia (25 major, 23 intermedia, and 24 minor) were evaluated. Patients older than 40 years and those with chronic kidney disease, diabetes mellitus, congestive heart failure, associated infections, congenital anomalies of the kidney and urinary tract were excluded. Blood and urine samples were collected electrolytes and markers of kidney function. Results. Mean age at the time of study was significantly higher in the minor group. The majority of patients with thalassemia major were males. Hematuria and pyuria occurred in 4% to 8% of the patients. Serum level of all variables were within normal limits, with no significant difference between the three groups. Glomerular filtration rate was nonsignificantly higher in the major and intermedia groups, compared to the minor variant. A significantly lower urine phosphorus and uric acid excretion was noted with the minor variant. Urine phosphorus and uric acid excretion increased more frequently in the major and intermedia groups. Conclusions. Tubular and glomerular functions appear to be well preserved in all variants of β-thalassemia.